Hydroxyapatite Nanorod-Modified Sand Blasted Titanium Disk for Endosseous Dental Implant Applications - Park, So Jung; Kim, Bo Su; Gupta, Kailash Chandra; Lee, Dong Yun; Kang, Inn-Kyu (Tissue engineering and regenerative medicine, 2018)
and blasted titanium (Ti) is commonly used in designing endosseous dental implants due to its biocompatibility and ability to form bonds with bone tissues. However, titanium implants do not induce strong interactions with teeth bones. To increase strong interactions between Ti disk implants and teeth bones, the l-glutamic acid grafted hydroxyapatite nanorods (nHA) were immobilized on albumin modified Ti disk implants (Ti-Alb). For modification of Ti disk implants by nHA, the l-glutamic acid grafted nHA was synthesized and then immobilized on albumin modified Ti disk implants. Fourier transformed infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscope; energy dispersive spectroscopy and confocal laser scanning microscopy were used to confirm the modification of Ti disk implants. The bioactivity of nHA-modified Ti disk implants was evaluated by seeding MC3T3-E1 cells on Ti-nHA implants. Characterization techniques have confirmed the successful modification of Ti disk implants by l-glutamic acid grafted nHA. The nHA-modified Ti disk implants have shown enhanced adhesion, proliferation and cytotoxicity of MC3T3-E1 cells in comparison to pristine Ti implants. The modification of Ti implants by l-glutamic acid grafted nHA has produced highly osteogenic Ti disk plants in comparison to pristine Ti disk implants due to the formation of bioactive surfaces by hydroxyapatite nano rods on Ti disk implants. Ti-nHA disk implants showed enhanced adhesion, proliferation, and MC3T3-E1 cells viability in comparison to pristine Ti disk implants. Thus nHA might be to be useful to enhance the osseointegration of Ti implants with teeth bones.